2008
DOI: 10.1016/j.bbamem.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Mutual effects of MinD-membrane interaction: II. Domain structure of the membrane enhances MinD binding

Abstract: Summary MinD, a well-conserved bacterial amphitropic protein involved in spatial regulation of cell division, has a typical feature of reversible binding to the membrane. MinD shows a clear preference for acidic phospholipids organized into lipid domains in bacterial membrane. We have shown that binding of MinD may change the dynamics of model and native membranes (see accompanying paper [1]). On the other hand, MinD dimerization and anchoring could be enhanced on preexisting anionic phospholipid domains. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…We propose that the mechanical stress in the membrane structure caused by binding of the initiation or dissociation centers affects the affinity of the membrane in the neighborhood of the complex to additional protein binding. Distortion of the membrane structure by MinD binding has been evidenced by the previous observation that unilamellar vesicles are converted to thin tubes by high-density binding of MinD (32), as well as recent fluorescence anisotropy and calorimetry studies of MinD interactions with lipid membranes (37,38). The above "membrane stress" hypothesis also explains additional aspects of our results as discussed below.…”
Section: Discussionsupporting
confidence: 64%
“…We propose that the mechanical stress in the membrane structure caused by binding of the initiation or dissociation centers affects the affinity of the membrane in the neighborhood of the complex to additional protein binding. Distortion of the membrane structure by MinD binding has been evidenced by the previous observation that unilamellar vesicles are converted to thin tubes by high-density binding of MinD (32), as well as recent fluorescence anisotropy and calorimetry studies of MinD interactions with lipid membranes (37,38). The above "membrane stress" hypothesis also explains additional aspects of our results as discussed below.…”
Section: Discussionsupporting
confidence: 64%
“…Possibly, the membrane potential results in a subtle conformational change of the amphipathic helix that enhances binding. On the other hand, it has been shown that binding of MinD is stimulated when the membrane fluidity is increased (27). Interestingly, membrane fluidity can also be increased by imposing a ΔΨ (28).…”
Section: Resultsmentioning
confidence: 98%
“…The co-localization of MadR1-GFP foci and FM 4–64 Fx hotspots indicates a connection between MadR1 activity and anionic phospholipid domains. MadR1 may localize to pre-established domains for activation as has been observed for several other membrane-associated proteins, or may stimulate the production of acidic phospholipids [3132]. It is possible these co-localized hotspots are due to the formation of lipid bodies resulting from protein overproduction or GFP fusion, however certain behaviors are unlikely to be attributed to lipid bodies.…”
Section: Discussionmentioning
confidence: 99%